Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

What I did


$(a+bi)^2 = 3-4i$

$a^2-b^2+2abi = 3-4i$

Then got 2 simultaneous equations

$a^2-b^2=3$ and $2ab=-4$

Solve for $a^2$ in 1st equation: $a^2=3+b^2$

Subbed into 2nd equation to power of 2



Is there a better way than below? Solving power 4 equation then cubic?

Then solved solved power 4 equation ...



then solved for cubic equation, getting ...



$b=\pm 1 \text{ or } 2i$

What did the book do now?

I did: (subbing into $a^2=3+b^2$)

When $b=1, a^2=3+1^2 \Longrightarrow a = 2$

When $b=-1, a^2=3+(-1)^2 \Longrightarrow a=2$

When $b=2i, a^2=3+(2i)^2=3+4(-1)=-1, a=i$

So I will have 3 equations

  • $2+i$ // why is this not in the book?
  • $2-i$
  • $i-2$

UPDATE (In response to @David Mitra)

Ok. I let $x=a^2$ and $b=b^2$ giving the quadratic equation: $x=3+y$ and $xy=4$. Then (after subbing) $(y-1)(y+4)=0$

Then when $y=1, x=4$. $y=-4, x=-1$

Then $b=\pm 1 or \pm 2i$ and $a=\pm 2i or \pm i$

Finally testing equations:

$(2+i)^2 = 3+4i$ (rej)

$(2-i)^2=5$ what to do?



... 8 equations (but 4 unique)

share|cite|improve this question
put $b^2 = x$ and it reduces to a quadratice :) – user9413 Nov 21 '11 at 8:25
up vote 5 down vote accepted

A better way to solve $ b^4+ 3b^2-4=0 $ is to write it as $(b^2 +4)(b^2 -1)=0$. This gives $b=1,-1,2i,-2i$. (Note, you missed $-2i$ in your write up.)

Then find the $a$ values as you did...

As for why $2+i$ wasn't in the answer key:

When you squared both sides of $ab=-2$ to get $a^2b^2=4$, you introduced new solutions. So in the end, you need to check which solutions you obtained work. This is why $2+i$ wasn't a solution to the original problem. In fact: $(2+i)^2=3+4i$.

In your last step, when solving for $a$ when $b=2i$, you obtain $a^2=-1$, so $a=i$ or $a=-i$ (you missed $-i$).

For $b=-2i$, you get again $a=i$ or $a=-i$.

This gives you four solutions that need checking: $-2+i, -2-i, 2+i, 2-i$.

Your update is off...

You are correct up to the point when you obtain $b^4+3b^2-4=0$. As I mentioned above, to solve this, write $$ b^4+ 3b^2-4=0 \iff (b^2 +4)(b^2 -1)=0\iff b=1,-1,2i,-2i. $$ For each of these $b$ values, we find the corresponding $a$ value(s):

For $b=1$: $a^2=3+1^2\Rightarrow a=2,-2$.

This gives $a+bi=2+i$

or $a+bi=-2+i$.

For $b=-1$: $a^2=3+(-1)^2\Rightarrow a=2,-2$.

This gives $a+bi=2-i$

or $a+bi=-2-i$.

For $b=2i$: $a^2=3+(2i)^2\Rightarrow a^2=-1\Rightarrow a=i,-i$.

This gives $a+bi=i+(2i)i=-2+i$

or $a+bi=-i+(2i)i=-2-i$.

For $b=-2i$: $a^2=3+(-2i)^2\Rightarrow a^2=-1\Rightarrow a=i,-i$.

This gives $a+bi=i+(-2i)i=2+i$

or $a+bi=-i+(-2i)i=2-i$.

So we have four possible solutions: $$ 2+i, 2-i, -2+i , -2-i $$

Now we check which of these is a solution to the original equation $(a+bi)^2=3-4i$. Taking the squares of the possible solutions: $$(−2+i)^2=3−4i, (−2−i)^2=3+4i, (2+i)^2=3+4i, (2−i)^2=3−4i.$$

So, there are two solutions: −2+i and 2−i.

share|cite|improve this answer
That is not the mistake. The quartic equation for $b$, although derived by squaring, is correct (because it could have been derived without squaring, using $ab = -2$) and all four of its solutions give valid pairs $(a,b)$. The error is in the words "subbing into $a^2 = 3 + b^2$". This will introduce two values of $a$ per value of $b$ when we know from $ab=-2$ that there is only one value of $a$ for each value of $b$. – zyx Nov 21 '11 at 9:12
The equation $ab=-2$ is not equivalent to $a^2b^2=4$. $a=-1, b=-2$ is a solution of the latter but not the former. – David Mitra Nov 21 '11 at 9:24
$(ab)^2$ was used only to write down the quartic for $b$, and does not introduce any extraneous solutions in the quartic (its four roots correspond to two copies of each correct value of the square root, not $\pm 2 \pm i$ as four putative roots of which two are shown false by "checking"). Squaring can be a source of extra solutions, but is not in this case. – zyx Nov 21 '11 at 9:36
OK I got $(-2+i)^2=3, (-2-i)^2=3, (2+i)^2=3+4i, (2-i)^2=5$ so I keep 3 equations? So the square of a square root of a complex number gives a "non-complex" number? – Jiew Meng Nov 21 '11 at 10:00
@jiewmeng, there is a mixture of basic and subtle problems here. The basic problems are to know how to square $(x+iy)$ (it will have both real and imaginary parts) which was written correctly in the question but wrong in the comment just now; also, the square root of a complex number is an ordinary complex number (or a pair of complex numbers each the negative of the other, just like $\sqrt{4} = \pm 2$). The subtle points are the ones discussed in the answers and comments, about extraneous solutions. – zyx Nov 21 '11 at 10:16

$b^4+3b^2-4=0$ is a quadratic equation in $b^2$, i.e. you can write $c=b^2$, and then the equation says $c^2+3c-4=0$. If you know how to solve quadratic equations, you've got it.

share|cite|improve this answer

The value of $a$ is calculated incorrectly when $b=1$. From $2ab=-4$ there is a unique value of $a$ for every value of $b$. When $b=1$, $a$ can only have the value $-2$ (not $+2$ as stated in the question), and then $z = i - 2$.

The quartic equation for $b$, although derived by squaring, is correct and is not responsible for introducing any extra solutions. It could have been derived without squaring, using $ab=−2$. The error is in the step "subbing into $a^2=3+b^2$ ". That quadratic equation derives two values of $a$ from each value of $b$, when we know from $2ab=−4$ that there is only one value of $a$ for each value of $b$. If $2ab=-4$ had been used for the determination of $a$ from $b$ no extra solutions would appear, and every value of $b$ would determine a correct value of $a$.

What did the book do now?

The book does not say, but I guess it meant: eliminate one of the variables using $xy = -2$, obtaining a quartic (degree 4) equation in the other variable that is a quadratic equation in $x^2$ (or $y^2$, whichever is the surviving variable). The quartic has two real and two imaginary roots. Where the book says there are two solutions, that means solutions with real values of $x$ and $y$. These can be found by taking the two real solutions of the quartic and solving for the other variable through $xy=-2$; if one variable is real, the value found for the other variable will also be real.

share|cite|improve this answer

You can look at this as a problem in the arithmetic of the Gaussian Integers, $\mathbb Z[i]$. I’ll make use of the fact that this ring is a Unique Factorization Domain, and I’ll also use the fact that every prime $p\equiv1\pmod4$ is writable as the sum of two squares, $p=m^2+n^2$, equivalently, $p=(m+ni)(m-ni)$, and that $m\pm ni$ are primes in $\mathbb Z[i]$.

For the prime $5$, the first where these facts become operative, we have $5=1^2+2^2=(1+2i)(1-2i)$, and certainly the two factors are not related by a unit, so that they generate different prime ideals of the G-Integers. What about $3+4i$? We have $(3+4i)(3-4i)=25=(1+2i)^2(1-2i)^2$, a product of primes in the UFD $\mathbb Z[i]$. Up to units, you see that it must be that $3+4i$ is equal to $(1+2i)^2$ or $(1-2i)^2$. You check, and you see that you don’t need to worry about units, and the first possibility is the right one.

share|cite|improve this answer

3-4i=4-4i+i^2=(2-i)^2, therefore square root of (3-4i)=+/- (2-i), The equation (z+1-2i)^2=(2-i)^2, therefore z+1-2i=+/- ( 2 - i) at first z+1-2i=2-i z = 1+i at second z = -3 + 3i

share|cite|improve this answer
Welcome to MSE! It really helps readability to format answers using MathJax (see FAQ). Regards – Amzoti Jun 15 '13 at 4:19

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.